Post-translational modifications as a key mechanism for herpes simplex virus type I evasion of host innate immunity - Yongxing Zhang; Junlei Xie; Ying Feng; Abdul Qadeer; Shanni Li; Xu Deng; Lipeng Zhu; Bo Kong; Zanxian Xia; Zanxian Xia (Frontiers in Microbiology)
Herpes simplex virus type 1 (HSV-1) is a DNA virus that infects humans and establishes long-term latency within the host. Throughout its prolonged interaction with the host, HSV-1 evades the innate immune system by encoding its own proteins. Post-translational modifications (PTMs) of these proteins play crucial roles in their function, activity, and interactions with other factors by modifying specific amino acids, thereby enabling a diverse range of protein functions. This review explores the mechanisms and roles of PTMs in HSV-1-encoded proteins, such as phosphorylation, ubiquitination, deamidation, and SUMOylation, during HSV-1 infection and latency. These modifications are essential for suppressing host innate immunity, facilitating viral replication, and elucidating the crosstalk among various post-translational modifications.